Business Intelligence and Data Warehouse in Data Management for Decision Making in Different Companies: A Review of the Scientific Literature From 2015 – 2020 - Kevin Cabrera-Rojas; Alexandra Chavez-Gallardo; Michael Cabanillas-Carbonell (Communications of International Proceedings, 2021)
The research topic is oriented to the knowledge of new technologies, Business Intelligence and Data Warehouse, to improve data management and decision making. The study conducted is a review of the scientific literature, containing 67 articles from the databases: CROSBI, Hrčak, Dialnet, Digital Commoms, Taylor & Francis Group, IEEE Xplore, IOPscience, ScienceDirect, Scopus and from the Research Gate social network. According to the inclusion and exclusion criteria. Fifty articles were systematized. The purpose of the research is to demonstrate that the use of these new technologies, Business Intelligence and Data Warehouse, allow an efficient management of information to make informed decisions in time and meet the objectives of the company.
Keywords: Data warehouse; business intelligence; decision making; data management; systematic review.